Design of Grid Multi-Wing Chaotic Attractors Based on Fractional-Order Differential Systems - Lin, Yuan; Zhou, Xifeng; Gong, Junhui; Yu, Fei; Huang, Yuanyuan (Frontiers in Physics, 2022)
In this paper, a new approach is proposed for generating grid multi-wing chaotic attractors from the fractional linear differential system. The main idea is extending constructing heteroclinic loops approach from the classical differential equations to fractional differential equations for creating grid multi-wing attractors. By linearizing fractional Rucklidge system at its two symmetric equilibria to obtain two fundamental fractional linear systems, then constructing a heteroclinic loop to connect all equilibria of the above two fundamental fractional linear systems via saturated functions switching control. The numerical simulations confirm the effectiveness of the proposed method.